2019
DOI: 10.1186/s13071-019-3587-4
|View full text |Cite
|
Sign up to set email alerts
|

Killer yeasts exert anti-plasmodial activities against the malaria parasite Plasmodium berghei in the vector mosquito Anopheles stephensi and in mice

Abstract: Background Wickerhamomyces anomalus is a yeast associated with different insects including mosquitoes, where it is proposed to be involved in symbiotic relationships with hosts. Different symbiotic strains of W. anomalus display a killer phenotype mediated by protein toxins with broad-spectrum antimicrobial activities. In particular, a killer toxin purified from a W. anomalus strain ( Wa F17.12), previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 34 publications
0
52
0
2
Order By: Relevance
“…Parasite death is induced by the hydrolysis of the β-glucans located in cell-wall membranes of parasites. It was shown that yeasts could reduce the number of parasites (zygotes and ookinetes) by 65% [57]. Contrary to the observations made in vitro [56], no parasitic effect has been shown in vivo on oocysts and sporozoites.…”
Section: Direct Impact Through the Production Of Fungal Toxins Or Thementioning
confidence: 83%
See 2 more Smart Citations
“…Parasite death is induced by the hydrolysis of the β-glucans located in cell-wall membranes of parasites. It was shown that yeasts could reduce the number of parasites (zygotes and ookinetes) by 65% [57]. Contrary to the observations made in vitro [56], no parasitic effect has been shown in vivo on oocysts and sporozoites.…”
Section: Direct Impact Through the Production Of Fungal Toxins Or Thementioning
confidence: 83%
“…This killing mechanism, which could protect Anopheles mosquitoes from infection by entomopathogenic fungi, is partly based on an exo-β-1,3-glucanase enzymatic activity of the toxins [56]. Due to their presence in the midgut and the exo-β-1,3-glucanase enzymatic activity of their toxins, these W. anomalus strains strongly inhibit the development of Plasmodium berghei from gametocytes to ookinetes in females [57]. Parasite death is induced by the hydrolysis of the β-glucans located in cell-wall membranes of parasites.…”
Section: Direct Impact Through the Production Of Fungal Toxins Or Thementioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of live or heat-inactivated bacteria isolated from mosquito midgut significantly decreases the infection rate of P. falciparum [20]. Wickerhamomyces anomalus, a yeast involved in symbiotic relationships with Anopheles, is able to directly eliminate Plasmodium through secreting killer toxin [21,22]. Another stably inherited gut commensal bacteria, Asaia, can be genetically modified and directly inhibits pathogen development by secreting antiplasmodial effectors [23].…”
Section: Introductionmentioning
confidence: 99%
“…The symbiotic yeast Wickerhamomyces anomalus strain (WaF17.12), isolated from the malaria vector mosquito Anopheles stephensi, has shown strong in-vitro anti-plasmodial activity. Mosquitoes colonized with WaF17.12 developed 65.2% fewer parasites than the control group [181]. More recently, a symbiont microsporidian (Microsporidia MB ) that colonizes An.…”
Section: Naturally Occurring Symbiotic Microorganisms With Anti-pathomentioning
confidence: 99%